The Role of Educational Methods in Teaching Students to Think Independently in Literature Lessons - Bozorova Dilnur Ravub kizi (Zien Journals, 2023)
This article explains what the concept of "independent thinking" is and how important it is in forming a well-rounded person. Different methods and information about the thinking process, in particular, its type of independent thinking, are described
Keywords: Literature; teacher; education; quality education